A cross sectional study on health status of adolescents in urban field practice area of tertiary care hospital in central India - Nimje, Ashish T.; Gawande, Avinash V.; Narlawar, Uday W.; Padole, Wandana H. (International Journal Of Community Medicine And Public Health, 2023)
Background: Adolescence is defined by WHO as the age group of 10-19 years. In India, adolescents (10-19 years) constitute about 21.4 percent of the population, comprising one fifth of the total population. Adolescents are apparently healthy people but they may also have various kinds of problems. If they are to reach adulthood in a healthy state, then it’s necessary to analyze the common health problems prevalent in this age-group so that targeted and concerted services could be provided to them. Objective of current study was to assess the health status of adolescents in urban field practice area of tertiary care hospital in Central India. Methods: A community based descriptive cross-sectional study was conducted in urban field practice area of Government Medical College and Hospital Nagpur. House to house survey was conducted among 330 adolescents out of which 214 (64.84%) were male and 116 (35.16%) were female. Results: In present study most common morbidity found was dandruff in 127 (38.48%) adolescents followed by acne vulgaris in 102 (30.90%). Anemia was present in 52 (15.75%) of study subjects. Out of 237 morbid study subject, 114 (48.10%) study subjects had single morbidity followed by 2 and 3 morbidities in 52 (21.94%) and 63 (26.59%) respectively. About 8 (3.37%) study subjects had more than 3 morbidities. Conclusions: The present study shows that adolescents experience various health problems. Predominant morbidities observed in study subjects are dandruff (pityriasis capitis), acne vulgaris, anaemia, dental carries.